Printed dielectric-based organic diodes and transistors. (26th February 2016) - Gooden, Kristin; Laudari, Amrit; Knotts, Grant; Guha, Suchismita
Abstract: Inkjet and other forms of printing are now popular deposition techniques for the various layers in organic electronic devices, which are crucial for the development of large-scale, low-cost, and flexible electronics. Along with the ease of deposition, inkjet printing provides better control of the organic semiconductor–dielectric interface in field-effect transistors (FETs) and metal–insulator–semiconductor (MIS) diodes, compared to other deposition techniques. We compare the electrical characteristics of inkjet-printed and spincoated poly-4-vinyl phenol (PVP) dielectric layers in pentacene-based and 6, 13-bis(triisopropylsilylethynyl) (TIPS)-pentacene-based FETs and MIS structures. Printed PVP films provide a natural alignment for the growth of TIPS-pentacene, thus improving the interface. TIPS-pentacene on printed PVP shows an order of magnitude higher FET charge carrier mobility compared to TIPS-pentacene on spincoated PVP FETs. Capacitance–voltage and conductance–voltage investigations of the MIS structures yield a lower value for the interface trap density for the printed PVP TIPS-pentacene device compared to the spincoated PVP TIPS-pentacene diode. Thermally grown pentacene on printed and spincoated PVP shows similar performance in MIS and FET structures.